Effect of pinch-off welding on quality of food packaging bottle - Carneiro, O. S. (2007)
The objective of this study was to investigate the influence of processing parameters on the quality of the pinch-off welding of an ethylene-vinyl alcohol/polypropylene (EVOH/PP) six-layer bottle for tomato ketchup, evaluated in terms of its structure and properties imparted to the corresponding bottles. The pinch-off welding process was studied on coextruded blow moulded bottles by varying the mould temperature, the mould closing speed and the hold time according to a L9-Taguchi experiment design. It was observed that the mould closing speed is the more influential parameter, determining the layered structure at the pinch-off and the mechanical performance of the bottle. Better properties were obtained when the mould closing speed was set to the highest value allowed by the blow moulding equipment.